2005
DOI: 10.1111/j.1745-7254.2005.00128.x
|View full text |Cite
|
Sign up to set email alerts
|

Taurine inhibits ischemia/reperfusion-induced compartment syndrome in rabbits1

Abstract: Aim: To investigate effects of taurine on ischemia/reperfusion (I/R)-induced compartment syndrome in rabbit hind limbs. Methods: Rabbits underwent femoral artery occlusion after ligation of branches from terminal aorta to femoral artery. After a 7-h ischemia, reperfusion was established with the use of heparinized polyethylene shunts. Rabbits received taurine (1 g/kg) or normal saline (control) by iv infusion 10 min before shunt placement. During reperfusion, anterior compartment pressure (ACP) was monitored c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…Taurine is a well documented anti‐oxidant and hypolipidaemic agent. It has been suggested that taurine stabilizes biomembranes and scavenges free radicals 21 . The observation of reduced MDA levels in the present study could be related to the direct anti‐oxidant effects of taurine.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Taurine is a well documented anti‐oxidant and hypolipidaemic agent. It has been suggested that taurine stabilizes biomembranes and scavenges free radicals 21 . The observation of reduced MDA levels in the present study could be related to the direct anti‐oxidant effects of taurine.…”
Section: Discussionsupporting
confidence: 59%
“…It has been suggested that taurine stabilizes biomembranes and scavenges free radicals. 21 The observation of reduced MDA levels in the present study could be related to the direct anti-oxidant effects of taurine. Because lipids are substrates for lipid peroxidation, a decrement in serum triglyceride levels could be another contributing factor to the reduced MDA levels.…”
Section: Discussionsupporting
confidence: 55%
“…It has been shown that taurine exhibits antioxidant effects and can decrease tissue oxidation caused by reactive oxygen species (ROS), decrease inflammatory activity with no known side effects, 35,36 and reduce ischemia-reperfusion–induced compartment syndrome in experimental settings. 37 Taurine supplementation could prevent mitochondrial damage and subsequent oxidative stress and improve perfusion outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Beneficial effects of taurine have been described in epilepsy, hypertension and diabettes [10]. It has been also demonstrated that treatment with taurine inhibits ischemia/reperfusion-induced compartment syndrome attenuating oxidative stress injury in rabbits [11]. Besides, we have recently shown that taurine prevents the inhibition of Na + ,K + -ATPase caused by GAA [12].…”
Section: Introductionmentioning
confidence: 95%